1989
DOI: 10.1126/science.2785716
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Buffering of Light-Evoked Potassium Increases by Retinal Müller (Glial) Cells

Abstract: Activity-dependent variations in extracellular potassium concentration in the central nervous system may be regulated, in part, by potassium spatial buffering currents in glial cells. The role of spatial buffering in the retina was assessed by measuring light-evoked potassium changes in amphibian eyecups. The amplitude of potassium increases in the vitreous humor was reduced to approximately 10 percent by 50 micromolar barium, while potassium increases in the inner plexiform layer were largely unchanged. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
123
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(135 citation statements)
references
References 19 publications
9
123
0
1
Order By: Relevance
“…At this concentration, Ba 2ϩ effectively blocks inward rectifier K ϩ channels (IRKs) that are highly expressed in glial cells (Newman, 1993). IRKs are thought to be involved in the spatial buffering of K ϩ released in the extracellular space during neuronal activity (Karwoski et al, 1989;Newman, 1993;Amédée et al, 1997;Kofuji and Newman, 2004). Because K ϩ accumulates in the glomerular layer after OSN stimulation (Jahr and Nicoll, 1981;Khayari et al, 1988;Friedrich and Korsching, 1998), the Ba 2ϩ -sensitive component is consistent with IRK-dependant current in response to extracellular K ϩ accumulation.…”
Section: Identification Of Glomerular Astrocytesmentioning
confidence: 81%
See 1 more Smart Citation
“…At this concentration, Ba 2ϩ effectively blocks inward rectifier K ϩ channels (IRKs) that are highly expressed in glial cells (Newman, 1993). IRKs are thought to be involved in the spatial buffering of K ϩ released in the extracellular space during neuronal activity (Karwoski et al, 1989;Newman, 1993;Amédée et al, 1997;Kofuji and Newman, 2004). Because K ϩ accumulates in the glomerular layer after OSN stimulation (Jahr and Nicoll, 1981;Khayari et al, 1988;Friedrich and Korsching, 1998), the Ba 2ϩ -sensitive component is consistent with IRK-dependant current in response to extracellular K ϩ accumulation.…”
Section: Identification Of Glomerular Astrocytesmentioning
confidence: 81%
“…Astrocytes are thought to use IRK channels to remove K ϩ from regions with high extracellular K ϩ and release it to regions with low K ϩ , a mechanism known as spatial buffering or siphoning of K ϩ (Karwoski et al, 1989;Amédée et al, 1997;Kofuji and Newman, 2004). In the retina, Kir4.1 channels are the main channels involved in the regulation of external K ϩ (Kofuji et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The supporting cell syncitium may act as a "sink" for excess perilymphatic K ϩ . Gap junction coupling could provide extensive spatial buffering, as seen in astrocytes (Leis et al, 2005) and retinal Müller cells (Karwoski et al, 1989). The widespread localization of gap junction channels, K/Cl cotransporters (Boettger et al, 2002), and aquaporins (Huang et al, 2002) could provide a passive mechanism of K ϩ buffering and osmotic homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, this phenomenon was confirmed in a variety of nervous tissue preparations (Kettenmann et al, 1983;Coles et al, 1986;Holthoff and Witte, 2000;Amzica et al, 2002). Although several possible mediators of astrocyte K ϩ uptake have been proposed, pharmacological studies suggest that K ir channels predominate in K ϩ buffering (Ballanyi et al, 1987;Karwoski et al, 1989;Oakley et al, 1992). The first identified glia-associated K ir was the weakly rectifying K ir 4.1 (Takumi et al, 1995), found in astrocyte processes surrounding synapses and blood vessels and in oligodendrocyte cell bodies (Poopalasundaram et al, 2000;Higashi et al, 2001;Ishii et al, 2003).…”
Section: Introductionmentioning
confidence: 99%